2013
DOI: 10.1590/s0100-204x2013000900003
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of cowpea genotype resistance to Callosobruchus maculatus

Abstract: -The objective of this work was to characterize the resistance of 50 cowpea (Vigna unguiculata) genotypes to Callosobruchus maculatus. A completely randomized design with five replicates per treatment (genotype) was used. No-choice tests were performed using the 50 cowpea genotypes to evaluate the preference for oviposition and the development of the weevil. The genotypes IT85 F-2687, MN05-841 B-49, MNC99-508-1, MNC99-510-8, TVu 1593, Canapuzinho-1-2, and Sanzi Sambili show non-preference-type resistance (ovip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…Similarly, dihybrid inheritance analysis of seed coat colour in pooled sampled seeds from both TVu11953 and Ife Brown mother plants also showed a significant deviation from the expected 1:2:1 ratio (Table 4). Cowpeas have been reported to show varied seed coat colours ranging from white to cream to brown to black each controlled by genes with maternal effects (Drabo et al, 1988;de Castro et al, 2013). These authors have showed that five major genes interact to produce ten different seed coat colours in cowpea.…”
Section: Segregation Of Cowpea Seed Coat Colourmentioning
confidence: 99%
“…Similarly, dihybrid inheritance analysis of seed coat colour in pooled sampled seeds from both TVu11953 and Ife Brown mother plants also showed a significant deviation from the expected 1:2:1 ratio (Table 4). Cowpeas have been reported to show varied seed coat colours ranging from white to cream to brown to black each controlled by genes with maternal effects (Drabo et al, 1988;de Castro et al, 2013). These authors have showed that five major genes interact to produce ten different seed coat colours in cowpea.…”
Section: Segregation Of Cowpea Seed Coat Colourmentioning
confidence: 99%
“…However, the use of synthetic insecticides to control bruchid infestation has widespread environmental contamination, toxicity to non-target organisms and negative effects on human health (Isman, 2008). The growing concerns about the harmful effects of pesticides have stimulated investigations in new, safer alternative pest control strategies, including the use of resistant genotypes (Castro et al, 2013;Tripathi et al, 2015). An understanding of the mechanisms of resistance to the bruchid is one of the key pre-requisites for designing effective and efficient strategies to breed resistant genotypes.…”
Section: Issn: 2320-5407mentioning
confidence: 99%
“…Several essays were developed in the scope of identifying the cowpea genotypes resistant to the attack of C. maculatus (Carvalho et al, 2011, Lima et al, 2001 Sci., Bom Jesus, v.10, n.1, p.150-157, Jan./Mar. 2019 Vilarinho 2011, Cajazeira 2000, Melo et al, 2012 without, however, investigating its causes (Castro et al, 2013). In this manner, this study aimed to evaluate the chemical composition of four cowpea cultivars concerning the preference and the development of Callosobruchus maculatus.…”
Section: Introductionmentioning
confidence: 99%